Study on the Deformation Law of the Embankment with Alluvial Fill in the Lower Yellow River - Chuanyi Ma; Xuanzheng Li; Chuan Wang; Daojun Deng; Quanyi Xie; Gaohang Lv (Advances in Civil Engineering)
In the dredging of the Yellow River, a common practice involves extracting alluvial fill from the river and depositing it on the rear side of the embankment, serving the dual purpose of river dredging and reinforcing the embankment. Nevertheless, there are few studies on the consolidation of alluvial fill extracted from the Yellow River. In this paper, laboratory experiments were conducted to examine the change in hydraulic conductivity during the consolidation process of the alluvial fill. Besides, a numerical model was established to investigate the dissipation law of excess pore water pressure and the settlement law of layered consolidation of alluvial fill. According to the research, the main conclusions can be drawn as follows: (1) During the consolidation process of the alluvial fill, the hydraulic conductivity exhibited a linear decline as the consolidation pressure increased. (2) The consolidation speed under the variable hydraulic conductivity case is lower than that on the condition when the hydraulic conductivity is constant. (3) In layered construction, the consolidation rate of alluvial fill decelerates with the augmentation of layers. Additionally, the dissipation rate of pore water pressure at the top of the alluvial fill surpasses that at the bottom. (4) Setting a geotextile mat can accelerate the consolidation speed and shorten the consolidation time of alluvial fill by 8.3%–30%.